Toxic Masculine Norms among Divorced Couples in Jordan - Tom, Dalal; Odeh Alsawalqa, Rula; Alhunaiti, Doukhi (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aims to reveal the level of compliance of divorced Jordanian men with toxic masculine norms, and to reveal the level of compliance of divorced Jordanian women with their ex-husbands' compliance with toxic masculine norms. Additionally, it aims to reveal the differences between the responses of divorced Jordanian couples toward the level of compliance with toxic masculine standards and each of the following variables: (age, employment status, number of years of marriage, number of years of divorce, educational level, income, number of children). Methods: The study applied the social survey method, and it chose an appropriate sample of (275) divorced men and women from the three regions (North, South, and Center) in the Hashemite Kingdom of Jordan. Results: The findings found that divorced Jordanian men comply with the toxic masculine norms of "exaggerated self-reliance", "violence and aggressive behavior", "masculine dominance and control", and "restrictive emotionality", respectively. Their level of compliance also increases as they age, the number of years they divorce, and the number of years they marry, while their level of compliance decreases with the increase in their level of education. Moreover, their level of compliance was not affected by their income level, employment status, or whether they had children or not. Conclusion: Toxic masculine norms constitute social pressures on men and dictate how to act like real men in a harmful way, requiring them to be violent, emotionally repressive, controlling, not asking for help, being overly self-reliant, and exercising their power over women and weaker men. Although men's compliance with these standards and characteristics made them common and normal in patriarchal societies, they still negatively affect both women and men and contribute to the termination of the marital relationship.